Joint association of sedentary behavior and physical activity with pulmonary function - Yiwen Wang; Yujie Xie; Yan Chen; Guodong Ding; Yongjun Zhang (BMC, 2024)
Abstract Background Sedentary behavior may influence the respiratory health, but the joint effects of sedentary behavior and physical activity on pulmonary function remains poorly elucidated. We aimed to estimate the association between sedentary behavior and physical activity with pulmonary function. Methods A total of 12,343 participants aged 12-79 years were analyzed from the U.S. NHANES 2007-2012. Participants were categorized into 16 groups according to the cross-tabulation of sedentary behavior time (0-4.0, 4.1-8.0, 8.1-12.0, and > 12.0 h/day) and moderate or vigorous physical activity (MVPA) (0, 1-149, 150-299, and ≥ 300 min/week). Generalized linear models were used to test the association of sedentary behavior and MVPA with pulmonary function. Results Participants with sedentary behavior > 4.0 h/day were negatively related to FEV1 (forced expiratory volume in 1 s) (β ranging from -0.015 to -0.009, p < 0.05). Compared with the reference group (0 min of MVPA and > 12.0 h/day of sedentary behavior), the negative association of sedentary behavior ≤ 8.0 h/day with FEV1 may be reduced through appropriate MVPA (β ranging from 0.019 to 0.030, p < 0.05). For sedentary behavior > 8.0 h/day, even MVPA ≥ 300 min/week may not decrease the negative relationships. Similar results were also observed in FVC (forced vital capacity) (β ranging from 0.018 to 0.030, p < 0.05). In participants aged ≥ 45 years, the associations were more notable. Conclusion This study indicated the sedentary behavior ≤ 4.0 h/day was a relatively healthy lifestyle for pulmonary function. Only below 8.0 h/day of sedentary behavior, the negative association with pulmonary function may be reduced through appropriate MVPA.